Velocity of powder particles in plasma at low pressure - Mrdak, Mihailo R. (Vojnotehnički glasnik / Military Technical Courier, 2018)
Low pressure of inert gas in the vacuum chamber significantly affects the transfer of plasma particle velocity onto powder particles, residence time of powder particles in plasma and the kinetic energy of molten particles before the collision with the substrate. In addition to low pressure of inert gas in the vacuum chamber, the size and mass density of powder particles, together with plasma arc power, have the biggest impact on the average velocity of powder particles. To measure the velocity of powder particles in the vacuum chamber at low pressure, a laser speedometer is applied.The average velocity of molten powder particles V=s/t is calculated when the length of the path of powder particles that pass between two focus distances of the laser beam is divided by the time of particle passage between the two focuses. Measurements are done for vacuum chamber pressure, the values of which are usually from 6.7 to 80 kPa. The paper describes the relationship between the average velocity of Al2O3 and W powder particles and the vacuum chamber pressure, granulate distribution, mass density and plasma arc power. It was found that, for powder of lower mass density, the average velocity of particles can increase for 200 m/s with a decrease in chamber pressure.The effect of pressure on W particles of larger mass density is lower but still important, because a decrease in pressure increases the average velocity of particles up to 50%. Reducing plasma arc power reduces the maximum velocity of both types of powder particles.